Applying knowledge translation frameworks, approaches and principles to co-create a dissemination plan: Optimizing the spread of a pediatric concussion guideline. (August 2022) - Provvidenza, Christine; Kingsnorth, Shauna; Dawson, Jennifer; Ledoux, Andree-Anne; Zemek, Roger; Reed, Nick
Background: Clinical practice guidelines are evidence-based statements that assist healthcare professionals with improving patient care. Achieving guideline aims depends on successful knowledge translation (KT) and includes dissemination and implementation efforts. Dissemination efforts are important precursors to implementation, help to maximize awareness and reach of best practices, and prepare for evidence adoption. This article shares the application of KT frameworks, approaches and principles in the creation of a dissemination plan and KT products for the Living Guideline for Pediatric Concussion Care . The target audience for dissemination are healthcare professionals delivering clinical care to patients between 5–18 years. Methods: Guided by the Framework for Knowledge Transfer and an integrated KT (iKT) approach, 46 concussion experts participated in an iKT workshop and knowledge board activity to: 1) establish a Living Guideline dissemination plan; 2) identify products to share the Living Guideline; and, 3) prepare for Living Guideline implementation planning. Post-workshop, a snowball approach invited knowledge users including educators and youth/young adults with lived experience in concussion via interviews and focus groups, to expand upon the dissemination plan and recommended products. Results: The dissemination plan yielded a reach of nearly 42, 000 Living Guideline page views from September, 2019-January, 2022. Dissemination efforts included 13 multi-media interviews, over 40 activities (e.g. webinars), and 28 engagement emails to help raise awareness. Eight KT products were developed to foster sharing and use of the Living Guideline, with over 3000 downloads across all KT products. Conclusions: Applying an iKT approach alongside appropriate frameworks and principles allowed for interaction and partnership building, resulting in the development of a robust dissemination plan and essential KT products. By showing the breadth and impact of the KT activities undertaken, it is hoped that the concussion community will explore how KT practices can bolster efforts to drive evidence into practice and optimize concussion care.